PENGARUH INFLASI DAN NILAI TUKAR RUPIAH TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DI BURSA EFEK INDONESIA (BEI) PADA MASA JELANG DAN SAAT PANDEMI COVID-19 - An-Nisa Soeni; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study aims to analyze the effect of inflation and the rupiah exchange rate on the Composite Stock Price Index (IHSG) on the Indonesian Stock Exchange (BEI) in the period leading up to and during the Covid-19 pandemic as measured using the Consumer Price Index (IHK), the exchange rate against the USD dollar. , the JCI average. The population in this study is all monthly time series data which includes the inflation rate, exchange rate and Composite Stock Price Index (CSPI) on the Indonesia Stock Exchange (IDX), the Central Statistics Agency (BPS) and Bank Indonesia (BI). The data analysis technique used is Multiple Linear Regression. This research hail shows that inflation has a positive effect on the JCI and the exchange rate has a negative effect on the JCI on the Indonesia Stock Exchange during and ahead of the Covid-19 pandemic. Keywords : Inflation, Exchange Rate and Composite Stock Price Index (JCI)